The effect of nitrates on thallium based oxycarbonate superconductors - Jones, M; Gameson, I; Edwards, P; Raveau, B (1998)
We have synthesised a series of compounds in both the (PbTl)Sr4Cu2O7(CO3) 1-y(NO3)y (0.1≤y≤0.5) and TlSr2Ba2Cu2O7(CO3) 1-y(NO3)y (0.1≤y≤0.2) systems. We report the synthesis conditions of these materials, an X-ray diffraction analysis of their structure and the changes induced in superconducting behaviour produced by the introduction of nitrate groups into the starting composition. © 1998 Plenum Publishing Corporation.